Organic phosphorus in the environment - Turner, B. L.; Baldwin, D. S.; Baldwin, D. S.; Frossard, E.; Frossard, E.; Turner, B. L. (Wallingford :CABI Publishing, 2005)
This book contains state-of-the-art reviews of organic phosphorus characterization and transformations in the environment. It includes 17 chapters organized into 3 main sections. Section 1 (3 chapters) describes analytical techniques used to characterize organic phosphorus compounds in environmental samples, with chapters dedicated to state-of-the-art procedures involving chromatographic separation, nuclear magnetic resonance spectroscopy and mass spectrometry. Section 2 (7 chapters) addresses the processes that control organic phosphorus behaviour in terrestrial and aquatic environments, including the origins, stabilization, hydrolysis (biotic and abiotic) and biological utilization of organic phosphorus. Section 3 (7 chapters) integrates these processes at the ecosystem level, with chapters synthesizing information on organic phosphorus in soils and aquatic systems, its interaction with other nutrient cycles and its transfer between terrestrial and aquatic environments. Two chapters (Chapters 15 and 16) in this section describe state-of-the-art models used to investigate the behaviour of organic phosphorus in both terrestrial and aquatic environments. The final chapter in this section summarizes the importance of organic phosphorus in the environment and identifies key areas towards which future research effort should be directed.
Keywords: FF061 - Plant Nutrition; JJ100 - Soil Biology; JJ200 - Soil Chemistry and Mineralogy; JJ600 - Soil Fertility; MM300 - Aquatic Biology and Ecology; PP200 - Water Resources; ZZ100 - Mathematics and Statistics; ZZ394 - Biochemistry and Physiology of Microorganisms, (New March 2000); ZZ900 - Techniques and Methodology